Oral manifestation and dental management of catch 22 syndrome - Kulan, Pınar; Namdar Pekiner, Filiz; Akyüz, Serap (Marmara Dental Journal, 2013)
The deletion of chromosome 22q11.2 is described as CATCH 22, Velocardiofacial Syndrome or Di George Syndrome. The acronym of CATCH 22 stands for cardiac defect, abnormal faces, thymic hypoplasia, cleft palate, hypocalcaemia but the acronym does not express all of the symptoms of CATCH 22 syndrome. Some clinical findings of CATCH 22 relate to congenital cardiac defects, velopharyngeal insufficiency with or without cleft palate, immune problems, feeding difficulties, hypocalcaemia, learning disabilities, behavioral abnormalities and lastly characteristic facial features. A treatment protocol of a 7-year-old child with CATCH 22 syndrome who also has dental caries complaint, toothache has been presented. Dental caries treatment and prophylactic application have been done for the patient. As a result, this study basically depicts how a dental approach can be followed for those patients who have CATCH 22 syndrome.
Keywords: CATCH 22 syndrome, FISH, thymic hypoplasia